Development and efficacy assessment of an intense pulsed light sterilization device for pickled fruits and vegetables - Wasuri, Boonthong; Chainok, Piyamas; Na Thaisong, Phinthida; Chainok, Bopit (Hasanuddin University Food Science and Technology Study Program, 2025)
This study presents the development and efficacy assessment of an intense pulsed light (IPL) sterilization device tailored for the pickled fruit and vegetable industry. The project aimed to (1) design and construct a compact IPL unit for industrial use, (2) validate its microbial reduction performance through laboratory and field testing, and (3) promote technology transfer via operational trials. The prototype integrates a xenon lamp, pulse generation circuit, conveyor belt, and control interface, allowing precise adjustment of exposure parameters. Experimental results showed over 90% microbial reduction within 120 seconds at an average light intensity of 1.7 mW/cm² and a frequency of one pulse per second. The findings demonstrate the device’s potential for improving food safety without compromising product quality. Furthermore, the study evaluates its industrial applicability, highlighting opportunities for broader adoption and scalability across production settings.